Rerrefino de óleo lubrificante usado - Desiderato, Paulo Renato Moretti [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The lubricant oil used in engines of internal combustion must be, periodically, changed. Its mainly function in the engines is to reduce the friction between the pieces, but its presence also promotes the cleanness and the refrigeration of the equipment. These attributions, at the end of some cycles of operation, make the oil to be dirty, that is, full of contaminating substances such as water, gasoline, diesel, additives, oxidized hydro-carbons and rests of metals, not being recommended, therefore, its discarding in the environment. Thus, all the used lubricant oil that leaves the automobiles engine has been thrust, waiting for a solution. The pollution generated by the discarding of a ton of used oil per day in the soil or in the rivers is equivalent to a domestic sewer of 40 thousand of people. The indiscriminate burning of the used lubricant oil generates significant emissions of metallic oxides, besides other toxic gases, like the dioxin and sulphur oxides. In this context, the mean objective of this essay was to effectuate the rerrefine of the used lubricant oil, aiming the increase of its life cycle and consequently contributing for the reduction of the environmental pollution. According to the used process, it was possible to get a rerrefine oil, of good quality, which physicistchemistries properties are in compliance with the norms of NBR and ASTM

O óleo lubrificante utilizado em motores de combustão interna deve ser periodicamente trocado. Sua função nos motores é, principalmente, a de reduzir o atrito entre as peças, mas sua presença também promove a limpeza e refrigeração do equipamento. Estas atribuições fazem com que ao fim de alguns ciclos de operação o óleo esteja sujo, ou seja, cheio de contaminantes, tais como água, gasolina, diesel, aditivos, hidrocarbonetos oxidados e restos de metais, não sendo recomendado, portanto, seu descarte no meio-ambiente. Assim, todo o óleo lubrificante usado que sai dos motores automotivos tem sido estocado, aguardando uma solução. A poluição gerada pelo descarte de uma tonelada por dia de óleo usado no solo ou em rios equivale ao esgoto doméstico de 40 mil habitantes. A queima indiscriminada do óleo lubrificante usado gera emissões significativas de óxidos metálicos, além de outros gases tóxicos, como a dioxina e óxidos de enxofre. Dentro deste contexto, o principal objetivo deste trabalho foi efetuar o rerrefino de óleo lubrificante usado, visando o aumento do seu ciclo de vida e conseqüentemente contribuindo para a diminuição da poluição ambiental. De acordo com o processo empregado, foi possível obter um óleo rerrefinado, de boa qualidade, cujas propriedades físico-químicas estão em conformidade com as normas da NBR e ASTM
Keywords: Oleos lubrificantes; Combustíveis para motores; Oxidos metalicos; Poluição; Oxidos de enxofre; Normas tecnicas; Lubricating oils; Motor fuels; Metallic oxides; Sulfur oxides; Pollution; Standardization